Place attachment and continuity of urban place identity - Ujang, Norsidah (Elsevier, 2009)
Place attachment contributes to the making of place identity. This paper focuses on place attachment and its significance in defining place identity of the main shopping streets in the city centre of Kuala Lumpur, Malaysia. A questionnaire survey and interviews were conducted to examine place attachment and place characteristics that influence it. This paper contributes in identification of place attachment constructs and place attributes that can be used as assessment indicators for future redevelopment of local urban places. It will benefit in securing place identity therefore, sustain attraction that will bring greater economic and tourism advantages to the city.